2004
DOI: 10.7326/0003-4819-140-3-200402030-00009
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Use of Postmenopausal Hormone Therapy after the Publication of Clinical Trial Results

Abstract: The release of the HERS data was temporally associated with a modest decline in the use of hormone therapy. In contrast, the release of the principal findings from the WHI was associated with a more substantial decline in use by postmenopausal women. The reason for the differences in decline may relate to the fact that the WHI results were widely publicized or were more applicable to most postmenopausal women because the WHI study was performed in healthy women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
152
3
3

Year Published

2004
2004
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(172 citation statements)
references
References 15 publications
14
152
3
3
Order By: Relevance
“…This percentage of current HRT users is somewhat higher than the 20% reported in 1999 in the general population in Great Britain, 43 but much lower than the estimated 41% of current users in a general population sample in the USA in 1997. 44 The combined number of current and past users in our sample (44%) is higher than in the USA sample of SCI women (35% preinjury and 26% postinjury), 40 but lower than the 60% reported in a 2002 British community survey of women aged 51-57 years. 45 The average duration of treatment in our sample was more than twice as long as in the general population, probably because almost half of the women on HRT in our study were taking it for osteoporosis prevention.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…This percentage of current HRT users is somewhat higher than the 20% reported in 1999 in the general population in Great Britain, 43 but much lower than the estimated 41% of current users in a general population sample in the USA in 1997. 44 The combined number of current and past users in our sample (44%) is higher than in the USA sample of SCI women (35% preinjury and 26% postinjury), 40 but lower than the 60% reported in a 2002 British community survey of women aged 51-57 years. 45 The average duration of treatment in our sample was more than twice as long as in the general population, probably because almost half of the women on HRT in our study were taking it for osteoporosis prevention.…”
Section: Discussioncontrasting
confidence: 61%
“…It is worth noting that the data collection for this study took place before the latest results of the Women's Health Initiative 2 and Million Women Study 20 were published. The proportion of women who decide to start or continue HRT may have changed since then, both in the general population 44,46 and in women with SCI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although menopause hormonal therapy is the most effective treatment for vasomotor and urogenital symptoms, the results of the Heart and Estrogen/Progestin Replacement Study (HERS) and the Women's Health Initiative (WHI) trials, which showed that the risks outweigh the benefits (3,4), dramatically altered the medical practices of such therapy (5). Despite a striking decrease in the use of menopause hormonal therapy, many women remain eligible for it.…”
Section: Systemic Lupus Erythematosus (Sle) Is An Autoimmune Disease mentioning
confidence: 99%
“…Because osteoporosis is a disease requiring long-term treatment if not prevented, women will likely need to be shifted from HT to other antiosteoporosis medications (AOMs) in order to continuously receive the beneficial effects of drug therapy on bone. Given the important therapeutic recommendations of the WHI publication and the documented impact of the study on HT use by several studies, [6][7][8][9][10][11] it is important to understand how these changes affect the management of osteoporosis in a vulnerable population, such as Medicaid recipients, with a lower socioeconomic status. The primary goal of this study was to evaluate the extent of osteoporosis prevention and treatment with AOM before and after release of the WHI results.…”
Section: Introduction Tmentioning
confidence: 99%